Geoquest Project Implementation and Experimentation of a Computer Classroom Role Playing Game: Final Results - Maraffi, Sabina; Sacerdoti, Francesco M. (European Scientific Journal, ESJ, 2019)
The GeoQuest Project started as a PhD research project in Teaching and Learning Processes in Science Education. It aims to answer to both students and teachers’ needs in an ever-changing world. Today, in particular, students need teaching tools that use different communication codes, as they are less accustomed to abstraction. An increasingly interconnected and technological world requires students to have specific skills: knowledge of the disciplines founding cores in an interdisciplinary key is required, along with technical and technological skills, mastery of foreign languages, flexibility, attitude to team working, creativity and entrepreneurship. Scientific subjects, such as Science, Technology, Engineering and Mathematics (STEM subjects) need to be strengthened and studied through a laboratory approach. On the other hand, teachers need user-friendly teaching tools, which allow and promote teamwork, which allow the laboratory teaching and the CLIL (Content and Language Integrated learning) approach. We have therefore developed a Computer Classroom Role Playing Game (CCRPG), GeoQuest, which has already been described in some international publications; a multi-phase experimentation was carried out for two years. In this paper, we illustrate the phases of experimentation, the excellent results achieved and the quantitative statistical analysis. The final outcome is how GeoQuest Project matches the students and teachers’ needs.